Testing the potential of zebularine to induce heritable changes in crop growth and development - E. Jean Finnegan; Peter A. Crisp; Peng Zhang; Judith Eglitis-Sexton; Julian Greenwood; Jessica Hintzsche; Jianbo Li; Jen Taylor; Xiaomei Wallace; Stephen Swain (Theoretical and Applied Genetics, 2025)
Key message Zebularine-treated wheat uncovered a phenotype with characteristics of an epigenetically regulated trait, but major chromosomal aberrations, not DNA methylation changes, are the cause, making zebularine unsuitable for epigenetic breeding. Abstract Breeding to identify disease-resistant and climate-tolerant high-yielding wheats has led to yield increases over many years, but new hardy, higher yielding varieties are still needed to improve food security in the face of climate change. Traditional breeding to develop new cultivars of wheat is a lengthy process taking more than seven years from the initial cross to cultivar release. The speed of breeding can be enhanced by using modern technologies including high-throughput phenomics, genomic selection, and directed mutation via CRISPR. Here we test the concept of modifying gene regulation by transiently disrupting DNA methylation with the methyltransferase inhibitor, zebularine (Zeb), as a means to uncover novel phenotypes in an elite cultivar to facilitate breeding for epigenetically controlled traits. The development and architecture of the wheat inflorescence, including spikelet density, are an important component of yield, and both grain size and number have been extensively modified during domestication and breeding of wheat cultivars. We identified several Zeb-treated plants with a dominant mutation that increased spikelet density compared to the untreated controls. Our analysis showed that in addition to causing loss of DNA methylation, Zeb treatment resulted in major chromosomal abnormalities, including trisomy and the formation of a novel telocentric chromosome. We provide evidence that increased copy number of the domestication gene, Q , is the most likely cause of increased spikelet density in two Zeb-treated plants. Collateral damage to chromosomes in Zeb-treated plants suggests that this is not a viable approach to epigenetic breeding.